Improving Students’ Creative Thinking Skills through Problem Based Learning on Colloid: A Lesson Study Practice - Munawaroh, Siti; Herunata, Herunata; Silviani, Silviani (Universitas Pendidikan Mandalika, 2025)
This study aims to improve students' creative thinking skills with Problem Based Learning (PBL) model assisted google sites on through lesson study practice on colloid topic. The research was conducted in the form of Classroom Action Research (CAR) over two open class cycles involving 34 students of class XI-C at state senior high school (SMAN) 2 Malang. The learning strategies used were mind mapping in cycle I and colloid-based product design projects in cycle II. Data were collected through observation sheets and creative thinking skills questionnaires based on Torrance’s indicators: fluency, flexibility, originality, and elaboration. The results showed a significant increase in the average score of students' creative thinking skills from 1.97 (fair) in cycle I to 2.64 (good) in cycle II. The highest improvement occurred in elaboration and flexibility indicators, while originality improved but remained in the fair category. These findings indicate that the integration of context-based digital media with the PBL model and reflective practices such as lesson study can gradually and significantly improve students' creative thinking skills.